A Robust Approach for Efficient Sodium Storage of GeS2 Hybrid Anode by Electrochemically Driven Amorphization. Issue 18 (12th March 2018) - Kim, Joo‐Hyung; Yun, Jong Hyuk; Kim, Do Kyung
Abstract: Sodium ion batteries (NIBs) have become attractive promising alternatives to lithium ion batteries in a broad field of future energy storage applications. The development of high‐performance anode materials has become an essential factor and a great challenge toward satisfying the requirements for NIBs, advancement. This work is the first report on GeS2 nanocomposites uniformly distributed on reduced graphene oxide (rGO) as promising anode materials for NIBs prepared via a facile hydrothermal synthesis and a unique carbo‐thermal annealing. The results show that the GeS2 /rGO hybrid anode yields a high reversible specific capacity of 805 mA h g −1 beyond the theoretical capacity, an excellent rate capability of 616 mA h g −1 at 5 A g −1, and a cycle retention of 89.4% after 100 cycles. A combined ex situ characterization study reveals that the electrochemically driven amorphization plays a key role in achieving efficient sodium storage by accommodating excess sodium ions in the electrode materials. Understanding the sequential conversion‐alloying reaction mechanism for GeS2 /rGO hybrid anodes provides a new approach for developing high‐performance energy storage applications. Abstract : The novel‐designed GeS2 /rGO hybrid anode materials are prepared via a facile hydrothermal synthesis and a unique carbo‐thermal annealing. The nanocomposites ensure the high reversible specific capacity of 805 mA h g −1 beyond the theoretical capacity and the excellent rate capability (562 mA h g −1 at 5 A g −1 ), revealing the best use of electrochemically driven amorphization.